The Contribution of Muallimah Putih to Islamic Education in Batu Bara Regency - Khairul Huda Imami; Azizah Hanum OK; Mohammad Al Farabi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze how educational institutions by Muallimah Putih and analyze the role of Muallimah Putih in the field of Islamic education. This type of research is qualitative research with a character study approach. Data collection techniques using interviews and document studies. The results of the research in this study are that the contribution of Mualliamh Putih in religious activities is the establishment of the first Islamic Educational Institution, RA Al-Ikhlas Indrapura Education Foundation, second, the Al-Ikhlas Indrapura TPA Education Foundation, and third, ?a?f?? al-Qur'?n educational foundation. Then as a teacher at various Batu Bara councils, as a preacher, and as the author of the manuscript are the Prayers of the Prophet Solomon and his Fadilah, Practices in the Month of Rajab, Practices of Ni?fu Sha'b?n, Things to Do Before Leaving for Hajj, Manners of Memorizing the Qur'an, Building a Happy Household, and Mustajab Prayers. Furthermore, the impact of the contribution of Muallimah Putih in Batu Bara Regency is that the Batu Bara Community is helped and grateful for the existence of Islamic Educational Institutions, the community and the Batu Bara congregation practice mustajab prayers, household arrangements, ni?fu sya'b?n practices, and the month of Rajab. Then the Batu Bara community also practices the manners of memorizing the Qur'an and manners before leaving for the Hajj as stated in the Muallimah Putih manuscript. The findings enrich the academic discourse on local Islamic educational leadership, particularly from a gender perspective, and highlight the intersection of institutional, cultural, and intellectual contributions. Practically, the study provides an applicable model for policymakers, educators, and religious organizations seeking to strengthen community-rooted Islamic education through inclusive and value-driven approaches.